Assisted Reproductive Technology and Anorectal Malformation: A Single-Center Experience - Iacusso, Chiara; Iacobelli, Barbara Daniela; Morini, Francesco; Totonelli, Giorgia; Viggiano, Milena; Caforio, Leonardo; Bagolan, Pietro (Frontiers in Pediatrics, 2021)
Background: Assisted reproductive technologies (ART) are becoming widespread, accounting for approximately 2% of all births in the western countries. Concerns exist on the potential association of ART with congenital anomalies. Few studies have addressed if a relationship exists between ART and the development of anorectal malformation (ARM). Our aim was to analyze the relationship between ARM and ART. Methods: Single center retrospective case control study of all patients treated for ARM between 2010 and 2017. Patients with bronchiolitis treated since 2014 were used as controls. Variables analyzed: prevalence of ART, gestational age, birth weight, maternal age. Patients with ARM born after ART were also compared to those naturally conceived for disease complexity. Fisher’ and Mann-Whitney test used as appropriate. Results: 369 patients were analyzed (143 cases and 226 controls). Prevalence of ART was significantly higher in ARM patients than in controls [7.6% vs 3.0%; odds ratio: 2.59 (95%CI 0.98-0.68); p=0.05]. Among ARM patients, incidence of VACTERL association (17%) is more frequent in ART babies. [1] Conclusions: Patients with ARM were more likely to be conceived following ART as compared to controls without congenital anomalies. Disease complexity of patients with ARM born after ART seems greater that those born after non-assisted conception.